Water-soluble fullerenes and molecular machines: Supramolecular approaches to nanomedicine - Rasovic, I (2019)
The incursion of the physical sciences into the medical sphere has led to myriad investigations in the use of nanomaterials for diagnostic and therapeutic purposes. In particular, the fullerenes show great promise in a number of areas because of their unique molecular properties. The chemistry of these carbon building blocks can be harnessed through covalent functionalisation and incorporation into supramolecular architectures such as extended self-assembled structures and molecular machines based on mechanically interlocked molecules. This thesis describes the synthesis and characterisation of such supramolecular structures incorporating fullerenes, whose potential utility in nanomedicine is demonstrated.